Milton, Marvell, and the Dutch republic - Van Raamsdonk, Esther, author.
1 online resource.
Keywords: "The tumultuous relations between Britain and the United Provinces in the seventeenth century provide the backdrop to this book, striking new ground as its transnational framework permits an overview of their intertwined culture, politics, trade, intellectual exchange and religious debate. How the English and Dutch understood each other is coloured by these factors, and revealed through an imagological method, charting the myriad uses of stereotypes in different genres and contexts. The discussion is anchored in a specific context through the lives and works of John Milton and Andrew Marvell, whose complex connections with Dutch people and society are investigated. As well as turning overdue attention to neglected Dutch writers of the period, the book creates new possibilities for reading Milton and Marvell as not merely English, but European poets"--